The Competitiveness of the Romanian Agri-Food Sector in the Context of Sustainable Development - Irina-Elena Petrescu; Mihai Istudor; Razvan-Aurelian Munteanu; Alexandra Nedelcu (Ovidius University Annals: Economic Sciences Series, 2023)
The agri-food sector in our country faces development gaps compared to other states in the European Union. The agricultural potential of our country is high and European Union finances this sector through the two pillars of the Common Agricultural Policy, namely market measures and rural development policy. The paper represents an analysis of GDP, population employed in agriculture, productivity and investments realized in the agricultural sector from Romania, in the period 2009 – 2021.